Identification and functional characterization of TNF receptor associated factor 3 in the sea cucumber Apostichopus japonicus. (June 2016) - Yang, Limeng; Chang, Yaqing; Wang, Yi; Wei, Jing; Ge, Chen; Song, Jian
Abstract: TNF receptor associated factors (TRAFs) are a family of proteins primarily involved in both adaptive and innate immunity. In this study, we identified a novel TRAF3 gene in Apostichopus japonicus by transcriptome sequencing and RACE approaches (designated as AjTRAF3 ). The full-length of AjTRAF3 was of 2796 bp including a 5′ untranslated region (UTR) of 83 bp, a 3′ UTR of 1066 bp and a putative open reading frame of 1647 bp encoding a polypeptide of 548 amino acid residues. The representative domains such as a RING finger domain (residues 54–96), two TRAF domains with zinc finger structure (residues 141–228), a coiled coil and a meprin and TRAF homology (MATH) domain (residues 396–522) were all detected in the deduced amino acids of AjTRAF3 . AjTRAF3 was ubiquitously expressed in all examined tissues with predominant expression in the body wall and slightly weaker in intestine, respiratory tree, tube feet, coelomocytes and longitudinal muscle. Time-course expression analysis in coelomocytes revealed that AjTRAF3 was significantly depressed towards Vibrio splendidus infection with a 0.20-fold decrease at 12 h, compared to control levels. AjTRAF3 silencing could elevate intracellular ROS levels by 2.08-fold and 2.09-fold compared to each control group in vitro and in vivo, respectively. Taken together, all these results suggested that AjTRAF3 may play a crucial role in the processes of anti-bacteria response in sea cucumber through regulating ROS production. Highlights: The full-length cDNA of TRAF3 was cloned from Apostichopus japonicus . AjTRAF3 was constitutively expressed in all tested tissues. AjTRAF3 could be depressed after Vibrio splendidus challenge in coelomocytes. AjTRAF3 silencing could elevate intracellular ROS levels in vitro and in vivo, respectively.